Hydrogen bonding induced enhancement for constructing anisotropic sugarcane composite hydrogels. Issue 46 (9th July 2021) - Xu, Rongnian; Zhao, Xiaoduo; Ma, Shuanhong; Ma, Zhengfeng; Wang, Rui; Cai, Meirong; Zhou, Feng
Abstract: Anisotropic hydrogels are appealing with their merits of similar biochemical and structural properties to the biological tissues. However, the mechanical properties of current anisotropic hydrogels need to be further improved. Herein, three kinds of novel anisotropic poly(2‐hydroxyethyl methacrylate) (pHEMA), poly(acrylamide) (pAM), and poly(acrylamide‐co‐acrylic acid) (p[AM‐co‐AA]) sugarcane composite hydrogels were prepared successfully by filling the hydrogel monomer precursor into porous aligned sugarcane nanofibers network and then performing subsequent free radical polymerization. The hydrogel matrix and sugarcane nanofibers network were combined closely together through hydrogen bonding interaction. The anisotropic sugarcane composite hydrogels exhibit good flexibility and elastic recovery properties upon encountering mechanical crimping and twisting. In typical case, the as‐prepared pHEMA sugarcane composite hydrogel can exhibit high anisotropic tensile strength of 2.37 and 0.54 MPa, while differential tear strength of 0.36 and 0.78 N/mm, along the parallel and vertical nanofibers directions. Finally, anisotropic lubrication behaviors were found and investigated systematically for those three kinds of sugarcane composite hydrogels when water was used as lubricant. Our current work proposes a simple and universal strategy for developing bioinspired anisotropic functional composite matters such as artificial skin, flexible sensor, and cartilage lubrication materials. Abstract : Three kinds of novel anisotropic sugarcane composite hydrogels are prepared by filling porous aligned sugarcane nanofibers sheet with pure hydrogels matrix based on network hydrogen bonding interaction. The as‐prepared anisotropic sugarcane composite hydrogels exhibit good flexibility and elastic recovery properties, compared to pure hydrogels matrix and pure sugarcane nanofibers sheet. Moreover, they present obvious anisotropic tensile strength, tear strength, and lubrication behavior.